Comparative Study of the Bioactivity of Two Bioceramic Materials - Trujillo-Hernández, Margarita (2018)
Calcium silicate-based materials have been shown to be bioactive due to their ability to produce biologically compatible carbonated apatite. The objective of this study was to analyze the bioactivity of Biodentine ™ and MTA Repair HP® in contact with human dentine discs, which were sealed and divided randomly to form four groups: group 1 Biodentine™, group 2 MTA Repair HP®, positive control group MTA Angelus® and negative control group IRM®, which were incubated in PBS solution for 10 days, for a subsequent analysis by means of MEB-EDS and Raman spectroscopy. The three calcium-based materials analyzed in this study proved to be bioactive because upon contact with a phosphate-based solution they were triggered at the onset of amorphous calcium phosphate, as the precursor during the formation of carbonated apatite.